Caribbean amphibians and reptiles - Crother, Brian I.; Schwartz, Albert, 1923-1992 (Academic Press, 1999)
Amphibians and reptiles are the most numerous, diverse, and frequently encountered animals on the Caribbean islands. This book provides a variety of perspectives on this amazing group of organisms. Caribbean Amphibians and Reptiles, compiled by an international team of zoologists, takes a fresh and detailed look at the complex biological puzzle of the Caribbean. The first true overview of the islands, it includes a historical examination of the people who have studied the Caribbean amphibians and reptiles. The book reviews the ecology, evolutionary history, and biogeographic explanations for the origins and diversity of the region's fauna with island-by-island coverage. It puts the Caribbean in perspective by comparing the islands to Central America and its amphibian reptile diversity. Additionally, the book includes figures, tables, and color plates which bring to life some of the region's most spectacular creatures. Key Features * Presents the first complete review of amphibians and reptiles in the Caribbean * Includes color plates and island maps * Contributors are recognized authorities in the field.